Estimation and Study of Contamination by Elements (Ni, Cu, Mg, Sn) in Dust of Areas near Fuel Stations in Najaf Governorate - Wisam Hassan Ali Alfartosi; Safa Saleem Zaye; Fatima Fahim Abd (International Journal of Pollution: Prevention & Control, 2025)
The research focused on studying and determining the levels of pollution in dust collected from various stations in the city of Najaf near fuel situations represented by four Fuel Situations (Soor Alnajaf Situation, Reebal Situation, Alkarar Situation, Alqudus Situation ), for this we selected 4 situations for current study, to determine the levels of pollution and compare them with the internationally permitted levels of elements (nickel, copper, and magnesium). Air pollution is one of the most dangerous types of pollution because it is difficult to control and address. However, air pollution has recently become a focus of attention as one of the most serious environmental problems facing the world, given its importance to our lives. Scientific studies and literature related to the concentration of heavy metals have focused on many important aspects of scientific research and have identified the role of industrial pollutants and smoke from fuel stations in increasing the concentration of many toxic and heavy metals. To reduce this pollution, numerous studies have been conducted to investigate the relationship between the concentration of heavy metals and many common diseases resulting from heavy metal pollution. To determine the concentration of heavy metals (Ni, Cu, Mg) in dust samples, we used a method to analyze and detect the concentration of metals in dust.
Keywords: Concentration; Pollution; Samples; dust; metals